A comprehensive dataset gathering 37 cover crop field experiments across France (2004–2022): plant and soil-related agronomic variables on 33 crop species from five botanical familieshttps://entrepot.recherche.data.gouv.fr - Manon Pull; Lionel Alletto; Eric Justes; Jay Ram Lamichhane; Elana Dayoub; Guillaume Hustet-Caou; Emilie Sitnikow; Noémie Gaudio; Pierre Casadebaig; Rémi Mahmoud; Neïla Ait Kaci Ahmed; Julie Constantin; et al. (Data in Brief)
Cover crops, sown between cash crops to provide ecosystem services, contribute to sustainability but present challenges related to the use of environmental resources out of the main cropping season. This dataset gathers the results of 37 field experiments related to cover crops, whether grown in sole crops or in mixtures, conducted in France over 19 years. It compiles quantitative data from field measurements and laboratory analyses on 33 species among five botanical families, along with information on technical management and climate conditions, providing a valuable resource for assessing cover crops performance.